The Development and Dynamics of Pesantren in Banten - Rohman Rohman (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2023)
This article explores the development and the dynamics of pesantren in Banten, a province located in the westernmost of Java. Using historical and anthropological data, I explore the development and dynamics of pesantren. I contend that some pesantrens in Banten not only function as religious educational institution but also to some extent function as political instruments in which the kyais or the leader of the pesantren nurture their Islamic views and interpretations based on their Islamic organization’s interests and agenda. Furthermore, I argue that pesantren in Banten based on their political view has developed into two main categories among others the Islamist dan non Islamist pesantrens that in short or longer period will pave the way to the existence of more plural views and religious authority for Bantenese as well as Indonesian Muslims.